The influence of bereavement on body mass index: results from a national Swedish survey. - Aldair J Oliveira; Mikael Rostila; Jan Saarela; Claudia S Lopes (PLoS ONE, 2014)
Background Previous findings suggest that the loss of a family member is associated with health and mortality. The purpose of this study was to investigate the association between bereavement experiences and BMI, and whether there are socio-demographic differences in this association. Objective To investigate the association between bereavement experiences and BMI, and whether there are socio-demographic differences in this association. Methods We used cross-sectional data with retrospective questions from the Swedish Level of Living Survey (LNU) of 2000, including 5,142 individuals. The bereavement experiences examined in the study include the loss of a sibling, a parent or a spouse, and time since the death of a parent. BMI (kg/m2) was calculated using self-reported measurements of weight and height. The association between bereavement and BMI was evaluated through linear regressions. Results After controlling for possible confounders, most of the models detected an association between bereavement and BMI. The fully-adjusted model showed that loss of parents was associated with a 0.45 increase in BMI (SE = 0.20). The effect also seemed to be dependent on time since the loss and social class position. Conclusions The present study is the first to examine associations between different types of familial losses and BMI. We find an association between the death of a family member and BMI, but it appears to be related to time since the death, type of bereavement experience and social class.